At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To solve the problem of finding the product [tex]\((x^2 + 3x + 1)(x^2 + x + 2)\)[/tex] and express the result in descending powers of [tex]\(x\)[/tex], follow these steps:
1. Multiply each term of the first polynomial by each term of the second polynomial:
- Start with [tex]\(x^2\)[/tex]:
[tex]\[ x^2 \cdot x^2 = x^4 \][/tex]
[tex]\[ x^2 \cdot x = x^3 \][/tex]
[tex]\[ x^2 \cdot 2 = 2x^2 \][/tex]
- Next, with [tex]\(3x\)[/tex]:
[tex]\[ 3x \cdot x^2 = 3x^3 \][/tex]
[tex]\[ 3x \cdot x = 3x^2 \][/tex]
[tex]\[ 3x \cdot 2 = 6x \][/tex]
- Finally, with [tex]\(1\)[/tex]:
[tex]\[ 1 \cdot x^2 = x^2 \][/tex]
[tex]\[ 1 \cdot x = x \][/tex]
[tex]\[ 1 \cdot 2 = 2 \][/tex]
2. Combine like terms:
- Collect all [tex]\(x^4\)[/tex] terms:
[tex]\[ x^4 \][/tex]
- Collect all [tex]\(x^3\)[/tex] terms:
[tex]\[ x^3 + 3x^3 = 4x^3 \][/tex]
- Collect all [tex]\(x^2\)[/tex] terms:
[tex]\[ 2x^2 + 3x^2 + x^2 = 6x^2 \][/tex]
- Collect all [tex]\(x\)[/tex] terms:
[tex]\[ 6x + x = 7x \][/tex]
- Constant terms:
[tex]\[ 2 \][/tex]
3. Write the final expanded expression in descending order:
[tex]\[ x^4 + 4x^3 + 6x^2 + 7x + 2 \][/tex]
Therefore, the product [tex]\((x^2 + 3x + 1)(x^2 + x + 2)\)[/tex] is:
[tex]\[ \boxed{x^4 + 4x^3 + 6x^2 + 7x + 2} \][/tex]
1. Multiply each term of the first polynomial by each term of the second polynomial:
- Start with [tex]\(x^2\)[/tex]:
[tex]\[ x^2 \cdot x^2 = x^4 \][/tex]
[tex]\[ x^2 \cdot x = x^3 \][/tex]
[tex]\[ x^2 \cdot 2 = 2x^2 \][/tex]
- Next, with [tex]\(3x\)[/tex]:
[tex]\[ 3x \cdot x^2 = 3x^3 \][/tex]
[tex]\[ 3x \cdot x = 3x^2 \][/tex]
[tex]\[ 3x \cdot 2 = 6x \][/tex]
- Finally, with [tex]\(1\)[/tex]:
[tex]\[ 1 \cdot x^2 = x^2 \][/tex]
[tex]\[ 1 \cdot x = x \][/tex]
[tex]\[ 1 \cdot 2 = 2 \][/tex]
2. Combine like terms:
- Collect all [tex]\(x^4\)[/tex] terms:
[tex]\[ x^4 \][/tex]
- Collect all [tex]\(x^3\)[/tex] terms:
[tex]\[ x^3 + 3x^3 = 4x^3 \][/tex]
- Collect all [tex]\(x^2\)[/tex] terms:
[tex]\[ 2x^2 + 3x^2 + x^2 = 6x^2 \][/tex]
- Collect all [tex]\(x\)[/tex] terms:
[tex]\[ 6x + x = 7x \][/tex]
- Constant terms:
[tex]\[ 2 \][/tex]
3. Write the final expanded expression in descending order:
[tex]\[ x^4 + 4x^3 + 6x^2 + 7x + 2 \][/tex]
Therefore, the product [tex]\((x^2 + 3x + 1)(x^2 + x + 2)\)[/tex] is:
[tex]\[ \boxed{x^4 + 4x^3 + 6x^2 + 7x + 2} \][/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.